2022
DOI: 10.1302/0301-620x.104b7.bjj-2021-1767.r1
|View full text |Cite
|
Sign up to set email alerts
|

20-year hip survivorship and patient-reported outcome measures after transpositional osteotomy of the acetabulum for dysplastic hips

Abstract: Aims Although periacetabular osteotomies are widely used for the treatment of symptomatic dysplastic hips, long-term surgical outcomes and patient-reported outcome measures (PROMs) are still unclear. Accordingly, we assessed hip survival and PROMs at 20 years after transpositional osteotomy of the acetabulum (TOA). Methods A total of 172 hips in 159 patients who underwent TOA were followed up at a mean of 21.02 years (16.6 to 24.6) postoperatively. Kaplan-Meier analysis was used to assess survivorship with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 36 publications
0
18
1
Order By: Relevance
“…Previous studies employed various PROMs to improve the quantification of a patient's experience following PAO; however, there is no consensus on which outcomes should be used. 8,10,[12][13][14][15] Wasko et al 12 analyzed the psychometric properties of hip-specific PROMs and found that the HOOS was most appropriate for patients undergoing PAO. However, HOOS consists of 40 items, hindering its routine use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies employed various PROMs to improve the quantification of a patient's experience following PAO; however, there is no consensus on which outcomes should be used. 8,10,[12][13][14][15] Wasko et al 12 analyzed the psychometric properties of hip-specific PROMs and found that the HOOS was most appropriate for patients undergoing PAO. However, HOOS consists of 40 items, hindering its routine use in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…While the long-term effectiveness of PAO in terms of finite endpoints, such as conversion to THA, has been demonstrated, [8][9][10] an accurate assessment of functional capacity and QoL may be more important for young, active patients undergoing PAO. The median FJS-12 of PAO patients in this study was considerably lower than the normative values for FJS-12 in the USA general population: a median FJS-12 score of 87.5 for the total sample and 79.5 for women in their fourth decade.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations